If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + -3s + s + 1 = 13 Reorder the terms: 1 + 3s + -3s + s = 13 Combine like terms: 3s + -3s = 0 1 + 0 + s = 13 1 + s = 13 Solving 1 + s = 13 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + s = 13 + -1 Combine like terms: 1 + -1 = 0 0 + s = 13 + -1 s = 13 + -1 Combine like terms: 13 + -1 = 12 s = 12 Simplifying s = 12
| 6x(2x+7)=48 | | 10j-j-2j=7 | | 4X+5=-2(X+3) | | 3x^2+18x-120= | | 25=9x+4-2x | | 3(p+2)=3(2p+4)+9 | | -3/4x=-9 | | 3(v-8)+-9=-6 | | 1-c=-7 | | -6x-5y=-27 | | 4X+5=2(-2X+4) | | -24=5g+15 | | -7m+9=26-2m | | 2(X+5)+6X=-27 | | -3x^2+18x=34 | | 3(h+8)=-18 | | 4X+5=-4X+6 | | 5x-(6x+6)=3x-50 | | 2(d-10)+2=-8 | | y+10x=8 | | 2(y+1)-15=5 | | 24x^4y+21x^3= | | 10(5+W)=-3(W+5) | | 2-4x=5x+20 | | 2030+5x=-15 | | -15k-7k+-10=12 | | 1/38=2.25/x | | 7/3-7i | | 5x-31=x+5 | | 9x+27x^2= | | -12n+16n+-19=-13 | | -3a+8b+61=0 |